The photodetection properties of a ruthenium electro-optic device for organic material-based device industry - Imer, Arife Gencer; Dere, Aysegul; Kaya, Esra; Al-Sehemi, Abdullah G.; Dayan, Osman; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2023)
The electrical properties and effect of illumination on the photodetection properties were investigated for the fabricated device with Ru(II)-pydim complex interface layer. The Ru(II)-pydim interface was deposited by spin coating technique on a p-silicon substrate. The electrical and optoelectrical parameters of photodiode were analyzed via the current-voltage (I-V), capacitance/conductance-voltage (C/G-V) measurements under dark and different illumination power. The fabricated device has good electrical parameters such as the rectification ratio of 2.726 x 104, the ideality factor of 1.328, and barrier height of 0.805 eV under the dark condition. The current values of the device with Ru(II)-pydim interface at reverse bias were strongly dependent on the illumination intensities, confirming its photoconduction behavior. The I-V measurements under different solar illuminations present that the electro-optic device with Ru(II)-pydim complex as an interface has good photodiode parameters with the responsivity of 131 mA/W, and the detectivity of 1.63 x 1011 Jones at 100 mW/cm2. The photo transient measurements demonstrate that the Ru(II)-pydim complex based photodiode presents the desired photo-switching property. Therefore, the prepared Ru(II)-pydim based device can be used for electro-optic and photonic applications, particularly in the rapidly developing organic material-based device industry.
Keywords: Photodiode; Ru(II)-Pydim complex; Illumination effect; Transient measurement